2012
DOI: 10.1097/wnr.0b013e32835688fe
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-induced expression of astrocytic thrombospondin-1 is regulated by P2 receptors coupled to protein kinase cascades

Abstract: Thrombospondin-1 (TSP-1) is an extracellular matrix protein produced by astrocytes, which can promote synaptogenesis. The regulation of astrocytic TSP-1 involves extracellular ATP through the activation of P2Y receptors coupled to various protein kinase signaling pathways. However, not much is known about the mechanisms regulating TSP-1 expression in primary cortical astrocytes after a traumatic brain injury. Using an in-vitro model of central nervous system trauma that stimulates the release of ATP, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In addition, TSP-1 expression is upregulated in the cortex after focal cerebral ischemia/reperfusion [20] and traumatic or hemorrhagic brain injury [21,22] and in the rat spinal cord after injury [23]. It is also confirmed that thrombin promotes the expression of TSP-1 in a rat model of intracerebral hemorrhage [21].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, TSP-1 expression is upregulated in the cortex after focal cerebral ischemia/reperfusion [20] and traumatic or hemorrhagic brain injury [21,22] and in the rat spinal cord after injury [23]. It is also confirmed that thrombin promotes the expression of TSP-1 in a rat model of intracerebral hemorrhage [21].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, astrocytic TSP-1 is involved in synaptogenesis [17] and has been implicated in neuronal dendritic growth and axonal sprouting [28,38]. The regulation of astrocytic TSP-1 by purinergic signaling suggests that purinergic signaling in astrocytes may play a vital role in the reorganization of synaptic networks after central nervous system injury, pointing to a key trophic role for astrocytes during and after brain trauma [22]. Because TSP-1 is a multifunctional molecule, much work may be required to make clear the exact effects of their expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TSP‐1 expression of animal cortex is upregulated after ischemic, traumatic, and hemorrhagic brain injury . It is also confirmed that thrombin promotes the expression of TSP‐1 in a rat model of intracerebral hemorrhage . Therefore, TSP‐1 may be released into the cerebrospinal fluid from damaged brain tissue and afterward escapes into the peripheral blood after brain injury.…”
Section: Discussionmentioning
confidence: 68%
“…It is likely that several signaling pathways can stimulate TSP production in reactive astrocytes. For example, in an in vivo trauma model, TSP1 expression was induced by extracellular ATP (Adenosine triphosphate) via P2Y purinergic receptors and ERK (extracellular signal-regulated kinase)/p38 MAPK (mitogen-activated protein kinase) signaling [119]. Additionally, TSP1 expression was activated by collagen-stimulated integrin signaling in reactive astrocytes following brain injury [120].…”
Section: Thrombospondinsmentioning
confidence: 99%